Evaluation of Antituberculosis Therapy In HIV/AIDS Patients at X Hospital Kudus - Elsa Latifatul Luthfi; Endang Setyowati; Intan Adevia Rosnarita (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aimed to evaluate the use of antituberculosis drugs (OAT) in HIV/AIDS patients with tuberculosis coinfection at X Hospital in Kudus by identifying patient characteristics, patterns of OAT and antiretroviral (ARV) use, and the rationality of OAT therapy using the Gyssens method. Research Method: This study used a descriptive evaluative design with a retrospective approach based on medical record data. The sample consisted of 41 HIV/AIDS patients with TB coinfection treated at X Hospital in Kudus during November 2024-November 2025, selected using total sampling. Data were analyzed univariately, while therapeutic rationality was assessed using the Gyssens method. Results and Discussion: Most patients were adults (92.7%) and male (82.9%). The most common OAT regimen was RHZE (4FDC) (70.7%), while the dominant ARV regimen was TLD (95.1%). All OATs were administered orally as tablets, and the duration of therapy was appropriate in all cases. The Gyssens evaluation showed rational OAT use in 95.1% of patients and irrational use in 4.9%, with inappropriate dosage as the main problem. Implications: These findings indicate that OAT prescribing practices were generally consistent with treatment guidelines, but body-weight-based dose adjustment still requires improvement. Further studies should explore the relationship between rational therapy, adherence, and clinical outcomes in TB-HIV patients.